(untitled) (Texas Journal of Medical Science, 2023)
Anemia of inflammation (AI), also known as anemia of chronic disease (ACD), is regarded as the most frequent anemia in hospitalized and chronically ill patients. It is prevalent in patients with diseases that cause prolonged immune activation, including infection, autoimmune diseases, and cancer. Given its frequency, it is second only to iron deficiency anemia. Rheumatoid arthritis is one of the most common types of chronic inflammatory arthritis. It is characterized by inflammation (pain, heat, swelling, redness) of the joints, especially of the hands and feet.